Exploring the influence of trust and perceived system quality on continuance intention toward e-filing system of Malaysian e-government service. A literature review - Ibrahim, Amlus; Chandra, Punitha (UUM College of Business, 2015)
In the current globalization arena, organizations are competing each others to survive in this era. At the same time government of each countries facing challenges and keep on finding the better ways to provide the better government services to the their stakeholders.Moreover, as the citizens become more internet savvy and have experienced of good quality of electronic services (e-services) from private sectors; this caused citizens' to expect the same high standards of e-services from government agencies in the delivery of public services.For that governments in each countries including Malaysia have been spent huge amount of money for the development of electronic government (e-government) and specifically in e-filing system to ease the government services.Thus, at this vein continuance intention towards e-government services deems to be important as ineffective usage of e-government service after initial adoption caused undesirable cost and waste of development of particular e-government service.